Stimulation of corticotrophin-releasing hormone release by the obese (ob) gene product, leptin, from hypothalamic explants. - Costa, A; Poma, A; Martignoni, E; Nappi, G; Ur, E; Grossman, A (1997)
Recent data have suggested that adipocytes synthesize and secrete a 16 kDa peptide which acts centrally to regulate weight gain by suppressing appetite and activating the sympathetic nervous system. To exert such effects, it may function as an endogenous ligand in the CNS, since specific receptors (OB-R) have been recently reported to be widely distributed in the brain. We have speculated that this peptide, now known as leptin, may act centrally by stimulating the release of corticotrophin-releasing hormone (CRH), a recognized potent inhibitory modulator of appetite. We tested in vitro the effect of murine leptin on CRH secretion in the dose range of 0.1 pM-100 nM. The static rat hypothalamic incubation system used involved fresh hypothalamic explants maintained in EBSS with consecutive 20 min incubations, and estimation of CRH concentrations in the medium by a specific and sensitive radioimmunoassay. The effect of heat-denatured leptin at a dose of 1 nM and 10 nM, was also investigated. Any possible modulation of leptin effects by adrenergic pathways was then explored by coincubating hypothalami with leptin 10 nM and equimolar concentrations of the alpha 1-adrenergic antagonist prazosin or the beta-adrenergic antagonist propranolol. The active leptin, but not the heat-inactivated peptide, caused a dose-dependent stimulation of CRH release in vitro (p < 0.05- < 0.0001 vs control), with a plateau effect at a dose of 10 nM. The addition of either prazosin or propranolol was without effect on leptin-dependent CRH stimulation. These findings are consistent with the reported presence of leptin receptors in the rat brain, and suggest that leptin may act to regulate appetite at least in part by directly modulating the secretion of CRH from the hypothalamus. It would also appear that such effect occurs via a non-adrenergic mechanism.